COMPREHENSIVE EVALUATION OF MISCIBLE GAS INJECTION METHODS FOR ENHANCED OIL RECOVERY AND CO2 EMISSIONS MANAGEMENT: A COMPARATIVE ANALYSIS OF EFFICIENCY AND SUSTAINABILITY (Experimental biology, 2025)
This study presents a comprehensive investigation into the effectiveness of gas-based enhanced oil recovery (EOR) techniques using CO₂, nitrogen, and hydrocarbon mixtures. To assess the minimum miscibility pressure (MMP), both theoretical calculations (PVTi analysis) and slim tube test simulations were employed, revealing significant discrepancies between the methods, particularly for CO₂ and ethane-containing mixtures. The results demonstrated that CO₂ and the hydrocarbon mixture CH₄–C₃H₈ exhibit the most favorable miscibility characteristics, enabling an optimal balance between technological efficiency and practical feasibility. Additionally, CO₂ demonstrated significant environmental benefits due to its potential for long-term storage in reservoirs as part of carbon capture and storage (CCS) technologies.To quantitatively evaluate the efficiency of the injectants, an integrated hydrodynamic model was developed using the Petrel – ECLIPSE 300 coupling, which accounted for reservoir filtration-capacity properties and fracture systems. The simulation results confirmed the superiority of CO₂ and hydrocarbon mixtures in terms of oil recovery and ...
Keywords: carbon capture and storage (CCS), CO2-EOR, sustainable oil production, phase diagram, minimum miscibility pressure, low-carbon technologies